(untitled) - Aaker, David A. (New York, 1995)
This book presents the methods and structures a manager needs to create and maintain an organizational environment that will promote both efficiency and an entrepreneurial spirit. Readers learn to describe and identify approaches to external analysis, sustainable competitive advantages (SCA), investment decisions and implementation
Keywords: Management,Quản trị